An efficient and rapid method for enrichment of lipophilic proteins from Mycobacterium tuberculosis H37Rv for two‐dimensional gel electrophoresis. Issue 9 (5th April 2016) - Sharma, Divakar; Bisht, Deepa
Abstract : Lipophilic proteome profiling is crucial because they have an anticipated role in biological processes and pathogenesis of Mycobacterium tuberculosis . These lipophilic proteins might be used as potential targets for the development of newer diagnostic markers and drug targets due to their association with membranes and drugs. We developed an efficient and rapid method to enrich the lipophilic proteins extraction from M. tuberculosis H37Rv for 2DE. In the extraction of lipophilic proteins, nonionic detergent (Triton X‐100) was added in sonication buffer that augmented the solubilization of the proteins at the time of sonication. Enriched whole cell lysate was subjected to direct phase separation using Triton X‐114, without the need for preisolation of membranes. In this study, we report that our optimized extraction buffer increased the lipophilic proteins extraction and their improved resolution on 2D gel up to two‐ to threefolds (quantitatively and qualitatively) as compared to standard extraction buffer. Some proteins were identified by MALDI‐TOF/MS.